2019
DOI: 10.3233/jsa-190328
|View full text |Cite
|
Sign up to set email alerts
|

Winning tennis matches with fewer points or games than the opponent

Abstract: Due to its unique scoring system, in tennis it is possible to win a match with fewer points or fewer games than the opponent. This scoring quirk has been called Quasi-Simpson paradox (QSP) and has been analyzed by Wright et al. (2013) for the years 1990-2011. This work follows up that of Wright et al. (2013) and extends it in that: i) the QSP is studied for different, and more recent, years (2012-2017), allowing a time comparison; ii) QSP is considered with respect to games as well as to points; iii) it consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A fundamental aspect of the C-ICC is its potential to address the hierarchical scoring system in volleyball, as also in tennis. This is known as the Quasi-Simpson paradox (Lisi et al, 2019) whereby the team with the lowest score can still win the match. Hence, not all points have the same importance, and the context of each event can make it more or less crucial for winning the match (Croucher, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental aspect of the C-ICC is its potential to address the hierarchical scoring system in volleyball, as also in tennis. This is known as the Quasi-Simpson paradox (Lisi et al, 2019) whereby the team with the lowest score can still win the match. Hence, not all points have the same importance, and the context of each event can make it more or less crucial for winning the match (Croucher, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Stanimirovic and Hanrahan [ 78 ] found that positive trends in the scoreboard or “momentum” were associated with psychological effects that affect performance. Similarly, sports like tennis with Simpson’s paradox scoring system [ 19 ] have shown a positive effect as a result of winning the previous point [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the high-level category was considered to be significantly more important by the experts (10/10 high load category versus 7/10 category attenuated load). This may be due to players tending to decrease their performance when they feel there is little chance of them winning and thus trying to save energy to more effectively recover for the next set [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and could therefore appear insignificant, but it is important to note that this is not the case. The outcome of a tennis match can be decided by tiny margins (O'Shannessy, 2017a); it is even possible to lose more points than an opponent in a match and still win, a phenomenon known as the Quasi-Simpson paradox (Lisi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%